BET 2: Blood biomarkers as an alternative to imaging in diagnosing acute ischaemic stroke. Issue 5 (19th April 2018) - Jane, Jessica; Lo, Ronson; Graham, Colin A
Abstract : A short-cut review was carried out to establish the diagnostic accuracy of blood biomarkers as an alternative to imaging for the diagnosis of ischaemic stroke. Nine studies were directly relevant to the question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that that blood biomarkers are currently not suitable for the diagnosis of acute ischaemic stroke.